(untitled) (Revista de Ciências Agroveterinárias, 2013)
This study aimed to develop and test a grafting technique for cloning feijoa plants (Acca sellowiana). The technique consisted of grafting young vegetative shoots of the scion on equally young rootstock, both with a diameter ranging from 0.3 to 0.5 cm. The rootstocks were selected from seedlings of the feijoa collection of Lages Experimental Station, Epagri. The scion wood was selected from feijoa plants of the same mentioned collection. The grafts were done under controlled conditions during the growing season (spring). The results suggest that the technique is efficient for cloning feijoa plants, presenting an average grafting success index of 92%.